2020
DOI: 10.1093/neuros/nyaa078
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Cervicothoracic Junction During Posterior Cervical Decompression and Fusion: Is It Necessary?

Abstract: BACKGROUND Posterior cervical fusion (PCF) is performed to treat cervical myelopathy, radiculopathy, and/or deformity. Constructs ending at the cervicothoracic junction (CTJ) may lead to higher rates of adjacent segment disease, and much debate exists regarding crossing the CTJ due to paucity of data in the literature. OBJECTIVE To determine whether extension of PCF constructs across the CTJ decreases incidence of adjacent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 15 publications
3
46
2
Order By: Relevance
“…The incidence of postoperative progression reported in the literature varied from 3.3% to 74.5%. [20] As Sakai K et al presented, postoperative progression of OPLL was observed in 5% of the anterior decompression and fusion with oating method group and 50% of the laminoplasty group. [21] Lee et al reported that the incidence progression of OPLL was 45.5%, 62.5%, and 30% for laminoplasty, laminectomy, and laminectomy with fusion, respectively.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The incidence of postoperative progression reported in the literature varied from 3.3% to 74.5%. [20] As Sakai K et al presented, postoperative progression of OPLL was observed in 5% of the anterior decompression and fusion with oating method group and 50% of the laminoplasty group. [21] Lee et al reported that the incidence progression of OPLL was 45.5%, 62.5%, and 30% for laminoplasty, laminectomy, and laminectomy with fusion, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…The substantial difference between mobility in cervical and thoracic spine may amplify rates of adjacent segment disease at the cervicothoracic junction when multilevel cervical fusions are terminated in the lower cervical spine. [16,17] So, routine extension of posterior cervical fusions into the thoracic spine has been suggested. The bene ts of extension into the thoracic spine include greater surface area for the fusion mass and the larger screws typically employed in the thoracic spine which may offer greater construct rigidity and a more stable mechanical environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published 'in vivo' studies however provide contrasting evidences. Articles by Schroeder et al [41], Ibaseta et al [24] and Fayed et al [15] found that posterior cervical constructs ending at C7, have increased risks of adjacent segment disease, while Huang et al [22] and Lee et al [32] found no signi cant increase in adjacent segment disease when stopping the construct at C7. At the same time, instrumentations that cross the CTJ have been reported to be associated with increased operative times and intraoperative blood loss [15,22].…”
Section: Rods Constructsmentioning
confidence: 99%
“…Some studies suggest that there is a major increase in fusion rates if the construct is extended down to T1-however, there seem to be discrepancies in this evidence throughout the available literature. 9,[13][14][15] The length of the construct has not been reliably found to be associated with the incidence of ASD or pseudarthrosis cases.…”
mentioning
confidence: 99%